2004
DOI: 10.1074/jbc.m402496200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Thioredoxin System

Abstract: Thioredoxin-2 (Trx2) is a mitochondrial protein-disulfide oxidoreductase essential for control of cell survival during mammalian embryonic development. This suggests that mitochondrial thioredoxin reductase-2 (TrxR2), responsible for reducing oxidized Trx2, may also be a key player in the regulation of mitochondria-dependent apoptosis. With this in mind, we investigated the effects of overexpression of TrxR2, Trx2, or both on mammalian cell responses to various apoptotic inducers. Stable transfectants of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 83 publications
2
34
0
Order By: Relevance
“…Earlier reports (51,58,62) have suggested an important function of the thioredoxin system in redox regulation of cell growth. In our study, we found a significantly slower growth of the TrxR1-and TrxR2-overexpressing cells as compared with their controls.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports (51,58,62) have suggested an important function of the thioredoxin system in redox regulation of cell growth. In our study, we found a significantly slower growth of the TrxR1-and TrxR2-overexpressing cells as compared with their controls.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial thioredoxin sys tem may be essential for mammalian development because disruption of Trx2 gene in the mouse resulted in massive apoptosis during early embryogenesis and embry onic lethality [166]. However, overexpression of Trx2 or TrxR2, or both, does not necessarily improve cell survival or resistance to ROS promoting factors, indicating that perhaps an unidentified variable controls the effect of these proteins [167].…”
Section: Mitochondrial Ros Detoxifying Systemsmentioning
confidence: 98%
“…After removal of the solvent, the crude product was purified over silica gel using ethyl CH 2 Cl 2 /MeOH (v/v, 9:1) as the eluent to yield Mito-Naph as a yellow solid (0. 13 Synthetic Materials and Methods. All reactions were carried out under nitrogen atmosphere.…”
Section: ■ Conclusionmentioning
confidence: 99%